PENINGKATAN KAPASITAS MASYARAKAT DALAM UPAYA PENCEGAHAN INFEKSI KULIT DAN PRODUKTIVITAS EKONOMI MELALUI PELATIHAN PEMBUATAN SABUN-VCO DI DESA MINAESA MINAHASA UTARA - Hariyanto, Yuanita Amalia; Jayanti, Meilani; Lebang, Julianri Sari (Universitas Mataram, 2025)
Considering skin disorders can now spread through a variety of media, it is crucial for the public to understand skin health issues. Skin conditions are now among the most prevalent illnesses in coastal towns. People who live near the coast are more likely to experience skin health issues. Numerous elements, such as humidity, sun exposure, personal cleanliness, and water quality, contribute to this. The goal of this project is to teach the Minaesa Village community how to make liquid soap from VCO and to educate them about personal hygiene. On-the-job training is the approach used in the PKM. Direct field visits, identifying the partners' issues and requirements, offering solutions, conducting activities to satisfy the partners' needs, and evaluation are all part of this approach. The pH of the VCOLS soap manufactured is 7, which means that it satisfies quality criteria. According to the evaluation's findings, participants' knowledge increased by 86.5%. More than 82.2% of participants expressed pleasure with the VCOLS soap, according to the evaluation of the satisfaction questionnaire about the created soap, while 17.8% expressed no opinion. The findings of the perception survey of the VCOLS soap, on the other hand, indicate that no one itched after using it, 70% thought it was non-greasy, and 67.7% thought it was hydrating. The evaluation's findings indicate that participants' knowledge of skin care and soap-making methods has grown. According to the results of the perception questionnaire, participants have successfully produced liquid soap from VCO that satisfies quality standards. It is also envisaged that the expertise offered, particularly in the creation of liquid soap from VCO, can be further enhanced through the community service activities in Minaesa Village.